Attendance in cancer screening programmes in Italy (Italian Journal of Public Health, 2008)
Background: The European Community recommends mammography, cervical and colorectal cancer screeningprogrammes. In Italy, cancer screening programmes have been included in the Basic Healthcare Parameters (LivelliEssenziali di Assistenza) since 2001. Full national coverage of a population-based organized screening programmehas been planned for in Italy and is being implemented. Since 2005, the Ministry of Health - Department ofPrevention has formally charged The National Centre for Screening Monitoring (Osservatorio Nazionale Screening–ONS-) with monitoring and promoting screening programmes nationwide. Participation of target populations is akey indicator of the impact and efficacy of a screening programme in reducing cancer mortality.Methods: Attendance of invitees is one of the indicators calculated every year in the quality control of Italianscreening programmes. Data collection is organized by means of a structured questionnaire, sent by ONS tothe referent for data collection in each Region, who then returns the completed questionnaires to the RegionalCentre. Questionnaires are then sent to the National Centre. Logical and epidemiologic checks are performedat both levels. Every year ONS publishes reports on the results of the surveys. A feasibility study for a Nationaldata warehouse based on individual records is in progress. The national survey “Multiscopo sulle famiglie”and the Passi Study (Progetti delle Aziende Sanitarie per la Salute in Italia) provided additional informationregarding spontaneous preventive health care activities in the Italian population.Results: Mammography screening: In 2006, 78.2% of Italian women aged 50-69 lived in areas whereorganised screening was in place (theoretical extension), however, the distribution of the screening activity isnot uniform (higher in Northern/Central Italy compared with Southern/Insular Italy). Similar geographicaldistributions can be noted in the attendance rates (60.5% in the North of Italy, 56% in the Central area and38.3% in the South of Italy).Cervical cancer screening: From the data obtained by the 2006 survey, 93.5% of theoretical extension wasregistered in the Centre of Italy, 65% in the North and 65.5% or in the South of Italy. 38.5% of invited womenunderwent a Pap-test. A decreasing trend in participation can be observed from Northern (45.6%) to Central(35.7%), and to Southern (28.7%) Italy.Colorectal cancer screening: In 2006, theoretical extension of colorectal cancer screening in Italy was 44%,with significant differences in geographical distribution (66.1% in the North of Italy 48.5% in the Centre andabout 10% in the South of our country). About 907,000 people had a faecal occult blood test in 2006 (adjustedcompliance of 44.6%).Data from the survey “Multiscopo sulle famiglie” showed that organised screening activity can reduce socialinequalities of access to cancer screening, increasing screening utilization particularly in less educated people.Conclusions: Organised cancer screening programmes have been extended in recent years, improving theequity in the access to early diagnosis for the people invited. However, social and geographical inequalitiesstill remain.
Keywords: attendance; mammography screening; cervical cancer screening; colorectal cancer screening